Solid-state generation of high-frequency burst of bipolar pulses for medical applications - Luis Redondo (2019)
This paper describes the operation of a solid-state generator proposed to produce high-frequency bipolar high-voltage pulse bursts on resistive-type loads, intended for medical applications. The generator design is based on two independent solid-state unipolar positive Marx generators positioned back to back, where the load is placed between the outputs of the two generators. SiC metal-oxide-semiconductor field-effect transistors (MOSFETs) are used in order to allow high-frequency operation. A generator with two five-stage Marx generators is experimentally tested in order to deliver up to 5000-V/50-A bipolar pulses, with 500-ns-10-mu s pulse widths and 200-ns-10-mu s relaxation time between positive and negative pulses. The generator operates in the burst mode from 1 to 200 pulses, in excess of 500 kHz within the burst, which can have a repetition frequency up to 1 kHz limited by the input 1000-V/200-W power supply, with forced air cooling. Results, with resistive-type loads, for several single pulse and burst mode operations are presented and discussed.